Emotional Intelligence and Its Relationship with Perceived Stress and Antenatal Depression Among Primary Gravida Women. - Hafsa bibi; Ms. Parveen Akhter; Mr. Badil; Ms. Fatima Soomro; Syed Azmat Hussain Shah; Irum Qureshi (Medical Journal of South Punjab, 2024)
Objective: To assess the relationship of emotional intelligence with perceived stress and antenatal depression among primary gravida women. Methods: Using purposive sampling technique, 303 participants were examined. Validated tools; EPDS, SSEIT, and PSS-10 were used to assess antenatal depression, emotional intelligence and perceived stress respectively. Data was analyzed using SPSS 26.0; Descriptive analysis including frequencies, percentages and mean was performed along with Spearman rank correlation test was applied to identify significant correlations (p < 0.05). Results: Among 303 participants, mean EI score of 113.97±19.56 showed participants’ diversified emotional assessment, management, and utilization. 60.4% reported moderate stress with mean PSS- 10 score 16.92±6.08. EPDS mean score 12.48±5.19 (64.7%) reported depression and 14.2% suicidal ideation. Significant negative relationships exist between EI and PS (r = -0.621, p < 0.01) and depression scores (r = -0.549, p < 0.01). Additionally, PS significantly linked with AD (r = 0.667, p < 0.01). Conclusion: EI helps primigravida women manage stress and reduce AD. Results emphasize that higher EI is linked to decreased stress and depression. Thorough mental health assessment and EI training are recommended to reduce stress and antenatal depression including focused treatments to improve maternal mental health.